Scenario of Head Injury Patients in Tertiary Care Hospital of Nepal - Paudel, Subodh Sharma; Luitel, Ritesh; Bista, Anushruti; Baniya, Aashish; Panta, Dibya Jyoti; Shrestha, Bibhushana; Singh, Aditi (Journal of Nepal Health Research Council, 2020)
Background: The aim of the study is to find out the age and sex distribution, modes of head injury and correlate Glasgow Coma Scale with Computed Tomography in patients with head trauma in our center.Methods: A cross-sectional study was performed among 113 patients of acute head trauma presenting to Emergency department of our hospital for three months. The severity of the head injury was assessed on admission by the Glasgow Coma Scale score and categorized as mild, moderate, or severe head injury. Non contrast head computed tomography was obtained. Results: The mean age of patients studied in this study was 35.53 year in males and 32.1 year in female with male to female ratio being 1.86:1. The most common causes of head injury were road-traffic accident 58 (51%), falls 42 (37%) and physical assault 13 (12%). In our present study, 67 (59.3%) of patients had mild head injury, 27 (23.9%) had moderate head injury and 19(16.8%) had severe head injury. Our study shows presence of multiple lesions with depressed bone fracture of skull bone was associated with lower Glasgow Coma Scale. Significant association between Glasgow Coma Scale and computed tomography finding was seen (p<0.001). Conclusions: Glasgow Coma Scale is strongly associated with computed tomography in patients with head injury. Road traffic accident is the commonest mode of injury. Most present with mild head injury.Keywords: Computed tomography; Glasgow coma scale; head injury